The Immunogenicity and Safety of CYD-Tetravalent Dengue Vaccine (CYD-TDV) in Children and Adolescents: A Systematic Review - Raksheeth Agarwal; Mardiastuti H Wahid; Oliver E Yausep; Sharon Hanmy Angel; Angga W Lokeswara (Acta Medica Indonesiana, 2017)
Aim: to assess the immunogenicity and safety of CYD-tetravalent dengue vaccine (CYD-TDV) in children. Methods: comprehensive literature searches were conducted on various databases. Randomized-controlled trials on children with CYD-TDV as intervention were selected based on inclusion and exclusion criteria. Data extracted from selected trials included safety of vaccine and immunogenicity in terms of Geometric Mean Titres (GMT) of antibodies. Results:  six clinical trials were selected based on preset criteria. GMT values were obtained using 50% Plaque Reduction Neutralization Test (PRNT) and safety was semi-quantitatively assessed based on adverse effects. Additional data processing was done to obtain a better understanding on the trends among the studies. The results showed that the groups vaccinated with CYD-TDV showed higher immunogenicity against dengue virus antigens than the control groups. Safety results were satisfactory in all trials, and most severe side effects were unrelated to the vaccine. Conclusion: CYD-TDV is both effective and safe for patients in endemic regions. This gives promise for further development and large-scale research on this vaccine to assess its efficacy in decreasing dengue prevalence, and its pervasive implementation in endemic countries, such as Indonesia.